HELRATOR (HELM VIBRATOR): HELM YANG DAPAT MEMBANGUNKAN PENGENDARA MOTOR YANG MENGANTUK - Muhammad, Irwansyah; Darmawan, Harits; Sepastika, Satya Jalu; Nazalaputra, Mohamad Faridz; Hati, Ika Permata (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
HelRator prototype is expected to raise awareness of tired and sleepy motorcyclists giving the shock warning like vibration and noises in the head area. The used method is a timer program. In the early stage we collect data that will be used as the basic theory in the making of HelRator. The second stage is materials preparation needed for the next step. The third and fourth stage are the designing and manufacturing the helmet. The final stage is testing prototype, and the helm shall be of useful to give warning and raise the awareness of sleepy motorists.